Training Graduate Students for Psychodiagnostics in the Structure of Educational Outcomes Monitoring - Shashlova G.M., (Психологическая наука и образование (2007. Online), 2016)
The article focuses on the stages of professional skills development in graduate students within the module “Psychological Diagnostics inChildren” (master's programme in School Psychology) based on the requirements of the professional standard and aimed at providing effective screening (monitoring) of mental development in children and adolescents in order to reveal those in need of psychological help. The article addresses the issue of instructional content selection in the module that would allow undergraduates to develop the ability and willingness to conduct unassisted psychodiagnostics in the process of monitoring children’s educational outcomes. Also, the article discusses the specifics of sharing between a university and an educational institution the responsibility for developing competencies in students required for carrying out such professional activities as screening (monitoring), processing data, interpreting data, and presenting outcomes. These aspects of work are covered in relation to the documents regulating the educational process, for instance, the Federal State Standards in General Education.